Steroid resistance of airway type 2 innate lymphoid cells from patients with severe asthma: The role of thymic stromal lymphopoietin - Liu, Sucai; Verma, Mukesh; Michalec, Lidia; Liu, Weimin; Sripada, Anand; Rollins, Donald; Good, James; Ito, Yoko; Chu, HongWei; Gorska, Magdalena M.; Martin, Richard J.; Alam, Rafeul (Journal of allergy and clinical immunology, 2018)
Type 2 innate lymphoid cells (ILC2s) represent an important type 2 immune cell. Glucocorticoid regulation of human ILC2s is largely unknown. We sought to assess steroid resistance of human blood and airway ILC2s from asthmatic patients and to examine its mechanism of induction. We studied human blood and lung ILC2s from asthmatic patients and control subjects using flow cytometry and ELISA. Dexamethasone inhibited (P = .04) chemoattractant receptor–homologous molecule expressed on TH2 lymphocytes and type 2 cytokine expression by blood ILC2s stimulated with IL-25 and IL-33. However, it did not do so when ILC2s were stimulated with IL-7 and thymic stromal lymphopoietin (TSLP), 2 ligands of IL-7 receptor α. Unlike blood ILC2s, bronchoalveolar lavage (BAL) fluid ILC2s from asthmatic patients were resistant to dexamethasone. BAL fluid from asthmatic patients had increased TSLP but not IL-7 levels. BAL fluid TSLP levels correlated (r = 0.74) with steroid resistance of ILC2s. TSLP was synergistically induced in epithelial cells by IL-13 and human rhinovirus. Mechanistically, dexamethasone upregulated ILC2 expression of IL-7 receptor α, which augmented and sustained signal transducer and activator of transcription (STAT) 5 signaling by TSLP. TSLP induced mitogen-activated protein kinase kinase (MEK), c-Fos, inhibitor of DNA binding 3, phosphorylated signal transducer and activator of transcription (pSTAT) 3, and pSTAT5, molecules linked to steroid resistance. Dexamethasone inhibited c-Fos, inhibitor of DNA binding 3, and pSTAT3 but not pSTAT5 and MEK. The MEK inhibitor trametinib, the Janus kinase–STAT inhibitor tofacitinib, and the STAT5 inhibitor pimozide reversed steroid resistance of BAL ILC2s. Dexamethasone inhibited type 2 cytokine production by blood ILC2s. IL-7 and TSLP abrogated this inhibition and induced steroid resistance of ILC2s in a MEK- and STAT5-dependent manner. BAL fluid ILC2s from asthmatic patients with increased TSLP levels were steroid resistant, which was reversed by clinically available inhibitors of MEK and STAT5.